DAKWAH DALAM PERSPEKTIF MEDIA SOSIAL - Muh Nur Latief (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2018)
This paper discusses about da'wah in social media by exposing the material and method of da'wah for people universally. The process of this little simple dakwah was supposed to be able to convey the main points of Islamic teachings in full which include; aqidah, shariah and morals. In this modern era technology has become more sophisticated so as to facilitate the da'i to preach using technology in accordance with the situation and conditions so it will be easy for Muslims to get knowledge from the media. By using social media will encourage Muslims to broadcast religion and this will bring a positive impact audiences against the use of media for preaching. Social media can make people communicate with each other wherever and whenever, no matter how far they are, and no matter day or night.